1987
DOI: 10.1111/j.1365-2648.1987.tb01355.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing management of postoperative pain: use of relaxation techniques with female cholecystectomy patients

Abstract: The purpose of this study was to assess the effectiveness of two different relaxation techniques in the management of postoperative pain. The sample consisted of 40 women between the ages of 21 and 65 years who were undergoing elective cholecystectomy. Using an experimental design, participants were randomly assigned to four groups: an experimental group who received a taped recording of a rhythmic breathing exercise (RB); an experimental group who received a taped recording of Benson's Relaxation Technique (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
44
0
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 32 publications
6
44
0
2
Order By: Relevance
“…The positive effects at rest are generally consistent with those of other studies of abdominal, orthopaedic, and GYN surgical patients who were not studied during ambulation (Levin et al, 1987;Locsin 1981;Mullooly et al, 1988;Nilsson et al, 2001;Osterbrink & Evers, 2000;Updyke, 1990;Wells, 1982). In this INT group, significance was found at fewer ambulation points (3/6) than those in the primary ABD a study (6/6) or the GYN intervention study (6/6).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The positive effects at rest are generally consistent with those of other studies of abdominal, orthopaedic, and GYN surgical patients who were not studied during ambulation (Levin et al, 1987;Locsin 1981;Mullooly et al, 1988;Nilsson et al, 2001;Osterbrink & Evers, 2000;Updyke, 1990;Wells, 1982). In this INT group, significance was found at fewer ambulation points (3/6) than those in the primary ABD a study (6/6) or the GYN intervention study (6/6).…”
Section: Discussionsupporting
confidence: 79%
“…Previous investigators have generally reported that these interventions were effective, both individually and in combination, after abdominal cardiac, and GYN surgeries (Good, 1995;Good et al, 1999 a ;Good, Stanton-Hicks et al, 2000 b ;Locsin, 1981;Mullooly, Levin, & Feldman, 1988;Nilsson, Rawal, Unestahl, Zetterberg, & Unosson, 2001; Updyke, 1990;Voss & Good, 2004). Relaxation techniques, such as deep breathing and jaw relaxation, have reduced postoperative pain after abdominal surgery (Flaherty & Fitzpatrick, 1978;Good et al, 1999 a ;Levin, Malloy, & Hyman, 1987;Roykulcharoen & Good, 2004;Wells, 1982) and orthopaedic surgery (Osterbrink & Evers, 2000). Music resulted in fairly large effect sizes in early clinical studies of children and adults with various types of pain: orthopaedic, obstetric, cardiac, gynecologic, dental, and terminal illness (Standley, 1986;Standley & Hanser, 1995).…”
mentioning
confidence: 99%
“…In addition, there was a graded effect: the combination treatment was significantly more effective than the individual interventions at day 1 rest. The post-hoc UV findings at rest were similar to (Levin et al, 1987) who used Benson's relaxation technique, (Locsin, 1981(Locsin, , 1988) who used preferred music to reduce pain behavior, and Mullooly et al (1988) (n = 11), who used easy listening music and found effects for both components of pain on day 2, and only for distress on day 1. Group sizes of Ͼ100 (Table 1) were probably the reason the findings were more positive than those in small preliminary studies.…”
Section: Restsupporting
confidence: 60%
“…In some studies relaxation or music reduced reports of sensory and affective pain (Flaherty and Fitzpatrick, 1978;Lawlis et al, 1985;Levin et al, 1987;Mullooly et al, 1988;Miller and Perry, 1990), while in others they reduced only affective pain (Wells, 1982;Horowitz et al, 1984;Mogan et al, 1985), had different results on different measures of pain (Good and Chin, 1998), or on different postoperative days (Good, 1995;Good and Chin, 1998). In other studies relaxation or music had no effect on pain but reportedly, provided a relaxing and pleasant experience (Heitz et al, 1992;Zimmerman et al, 1996;Heiser et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Aiken & Henrichs, 1971;Flaherty & Fitzpatrick, 1978 ;Johnson, Morrissey & Leventhal, 1973 ;Johnson, Rice, Fuller & Endress, 1978a;Levin, Malloy & Hyman, 1987;Sime, 1976). Information provision has been the most frequently studied intervention (Anderson, 1987;Johnson, Fuller, Endress & Rice, 1978b;Johnson & Leventhal, 1974;Johnson e t al., 1973;Langer, Janis & Wolfer, 1975;Miller & Mangen, 1983;Vernon & Bigelow, 1974;Wallace, 1984;Wilson, 1981).…”
mentioning
confidence: 97%